TRPV6, TRPM6 and TRPM7 Do Not Contribute to Hair-Cell Mechanotransduction - Morgan, Clive P.; Zhao, Hongyu; LeMasurier, Meredith; Xiong, Wei; Pan, Bifeng; Kazmierczak, Piotr; Avenarius, Matthew R.; Bateschell, Michael; Larisch, Ruby; Ricci, Anthony J.; Müller, Ulrich; Barr-Gillespie, Peter G. (Frontiers in Cellular Neuroscience, 2018)
The hair-cell mechanotransduction channel remains unidentified. We tested whether three transient receptor channel (TRP) family members, TRPV6, TRPM6, and TRPM7, were necessary for transduction. TRPV6 interacted with USH1C (harmonin), a scaffolding protein that participates in transduction. Using a cysteine-substitution knock-in mouse line and methanethiosulfonate reagents selective for this allele, we found that inhibition of TRPV6 had no effect on transduction in mouse cochlear hair cells. TRPM6 and TRPM7 each interacted with the tip-link component PCDH15 in cultured eukaryotic cells, which suggested they might be part of the transduction complex. Cochlear hair cell transduction was not affected by manipulations of Mg2+, however, which normally perturbs TRPM6 and TRPM7. To definitively examine the role of these two channels in transduction, we showed that deletion of either or both of their genes selectively in hair cells had no effect on auditory function. We suggest that TRPV6, TRPM6, and TRPM7 are unlikely to be the pore-forming subunit of the hair-cell transduction channel.